2023
DOI: 10.1086/723574
|View full text |Cite
|
Sign up to set email alerts
|

A Reassessment of Monetary Policy Surprises and High-Frequency Identification

Abstract: High-frequency changes in interest rates around FOMC announcements are an important tool for identifying the effects of monetary policy on asset prices and the macroeconomy. However, some recent studies have questioned both the exogeneity and the relevance of these monetary policy surprises as instruments, especially for estimating the macroeconomic effects of monetary policy shocks. For example, monetary policy surprises are correlated with macroeconomic and financial data that is publicly available prior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(19 citation statements)
references
References 77 publications
1
18
0
Order By: Relevance
“…Our results show that high‐frequency rate changes around FOMC announcements are predictable with the information in conditional skewness, questioning their use as exogenous monetary policy surprises. Our findings are consistent with evidence on this type of predictability using information in macroeconomic and financial variables (Cieslak (2018), Bauer and Swanson (2023a, 2023b)).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Our results show that high‐frequency rate changes around FOMC announcements are predictable with the information in conditional skewness, questioning their use as exogenous monetary policy surprises. Our findings are consistent with evidence on this type of predictability using information in macroeconomic and financial variables (Cieslak (2018), Bauer and Swanson (2023a, 2023b)).…”
supporting
confidence: 92%
“…Such monetary policy surprises are typically calculated from intraday changes in money market futures rates over a tight window around the FOMC announcements (Gürkaynak, Sack, and Swanson (2005)). Several recent papers find that these high‐frequency rate changes are predictable using publicly available macroeconomic data, possibly due to incomplete information of market participants about the Fed's implicit policy reaction function (Cieslak (2018), Bauer and Swanson (2023a, 2023b)). We study the predictability of monetary policy surprises using rate skewness, complementing the analysis in Section II.A as high‐frequency interest rate changes closely correspond to (negative) excess bond returns.…”
Section: The Information In Conditional Skewnessmentioning
confidence: 99%
“…Given that our theoretical mechanism is centered on the complementarity between labor and energy, we compare the model impulse responses of labor and energy to monetary and fiscal policy shocks with the corresponding empirical impulse responses. To do so, we use the identified structural shocks in Romer and Romer (2004), Auerbach and Gorodnichenko (2012), Zubairy (2018), andBauer andSwanson (2022). We find that the theoretical responses in our benchmark model are largely consistent with the empirical responses.…”
Section: Business Cyclementioning
confidence: 59%
“…Bianchi et al (2022) documented large shifts in the parameters of the US monetary policy rule over the past few decades and concluded that infrequent changes in the monetary stance can lead to persistent shifts in the real interest rate and asset valuations. Bauer and Swanson (2023) estimated a time-varying monetary policy rule for the Fed using weighted recursive least squares and found that the Fed's response to both the inflation and output gap has increased over the past 3 decades. Using a ML estimation method, G€ urkaynak et al (2023) provided evidence that weak monetary rules not satisfying the Taylor principle lead to outof-control inflation.…”
Section: Jes 519mentioning
confidence: 99%